Coaching Clinic Teknik Dasar Fotografi untuk Mendukung Dokumentasi Penelitian Mahasiswa: Coaching Clinic Basic Photography Techniques to Support Student Research Documentation - Mulyani, Rahmawati Budi; Melhanah, Melhanah; Asi, Yanetri; Djaya, Adrianson Agus; Saraswati, Dewi; Pandriyani, Pandriyani; Wardhana, Vinsen Willi; Suhardi, Suhardi; Suryani, Julia Nanda; Manullang, Arnoldus J. B. (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Visual documentation is an essential part of the data collection process in scientific research. Documentation can help data become more understandable and unambiguous. An effective visualization can strengthen the credibility of the data, facilitate readers' or audiences' understanding of the research context, and support the validity of field or laboratory observations. Based on initial observations and informal interviews with several final-year students, it was found that most lacked basic photography skills, especially in scientific documentation. Therefore, a photography technique coaching clinic was conducted by the Community Service Team, the Agrotechnology Student Association of Palangka Raya University, and the Indonesian Phytopathology Association of Central Kalimantan Regional Command. The aim was to improve students' knowledge and skills in scientific documentation photography. The method used was blended learning (theory and direct practice), along with pre-test and post-test questionnaires. The training results showed a significant increase in participants' understanding of basic photography techniques. Knowledge of photo composition increased to 87.8%, the use of light and shooting angles to 96.9%, optimal use of photographic equipment to 90.3%, and the preparation of visual documentation in research reports to 86.2%. This indicates that participants no longer view photography as merely a supplement but as an integral part of the process of recording data, analyzing, and presenting results scientifically and communicatively.